Evaluating the Potential Environmental Benefits of Cold Recycling-Based Methods for Flexible Pavement Rehabilitation in Virginia. Issue 6 (June 2022) - Amarh, Eugene Annan; Santos, Joao; Flintsch, Gerardo W.; Diefenderfer, Brian K.
This paper describes a study conducted to quantify the potential environmental benefits of recycled asphalt pavement projects completed in Virginia. Three restorative maintenance projects were evaluated: (i) a 5-in. hot-mix asphalt (HMA) over 5-in. cold in-place recycling (CIR) with foamed asphalt stabilization; (ii) a 3.5-in. HMA over 5-in. CIR with emulsion stabilization; and (iii) one non-recycling structural overlay (5-in. HMA over an existing pavement). In addition, the following reconstruction projects—the first three constructed on primary roads and the last two constructed on interstates—were assessed: (i) a 2.5-in. HMA over 9.6-in. full depth reclamation (FDR) with asphalt stabilization; (ii) a 3.5-in. HMA over 9.0-in. cement stabilized FDR; (iii) a non-recycling reconstruction project (7-in. HMA over 12-in. aggregate base and subbase); (iv) a 6-in. HMA over 6-in. asphalt-stabilized cold central plant recycled layer over a 12-in. lime-stabilized FDR base; and (v) a non-recycling reconstruction project (8-in. HMA over 18-in. aggregate base and subbase). When considering exclusively cradle-to-laid system boundaries, the results show that pavement recycling projects used for interstate reconstruction and primary route restorative maintenance yielded lower global warming (GW) than non-recycling approaches. When considering the entire life cycle, the study found that approximately 98% of the total GW came from pavement–vehicle interaction that takes place during the use stage. Finally, to reduce GW, the Virginia Department of Transportation could encourage (or even incentivize) practices that improve the initial pavement smoothness for recycling projects and use structural designs that are expected to have a low annual deterioration rate.